A Unique Junctional Interface at Contact Sites Between the Endoplasmic Reticulum and Lipid Droplets - Choudhary, Vineet; Schneiter, Roger (Frontiers in Cell and Developmental Biology, 2021)
Lipid droplets (LDs) constitute compartments dedicated to the storage of metabolic energy in the form of neutral lipids. LDs originate from the endoplasmic reticulum (ER), with which they maintain close contact throughout their life cycle. These ER-LD junctions facilitate the exchange of both proteins and lipids between these two compartments. In recent years, proteins that are important for the proper formation of LDs and localize to ER-LD junctions have been identified. This junction is unique as it is generally believed to invoke a transition from the ER bilayer membrane to a lipid monolayer that delineates LDs. Proper formation of this junction requires the ordered assembly of proteins and lipids at specialized ER subdomains. Without such a well-ordered assembly of LD biogenesis factors, neutral lipids are synthesized throughout the ER membrane, resulting in the formation of aberrant LDs. Such ectopically formed LDs impact ER and lipid homeostasis, resulting in different types of lipid storage diseases. In response to starvation, ER-LD junction recruit factors that tether the vacuole to these junctions to facilitate LD degradation. In addition, LDs maintain close contacts with peroxisomes and mitochondria for metabolic channeling of the released fatty acids towards beta-oxidation. In this review, we discuss the function of different components that ensure proper functioning of LD contact sites, their role in lipogenesis and lipolysis, and their relation to lipid storage diseases.